Spadek wartości aktywów w Republice Białorusi - mechanizmy identyfikacji i zwrotu - Korotaev, Sergei (Loss of Assets Value in the Republic of Belarus - identification and Cost Reimbursement Mechanism, 2005)
Rates of capital assets depreciation are necessary to determine a real assets value in a unit andthey should be determined for the end of the year as applicable. Furthermore, the units ought to havethe right to establish certain rates during a year in case of real deviation of book value from its marketone. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 289-295